Polishing composition, polishing method, and method for producing substrate
By using abrasive composition with low silanol-based density silica particles and specific structural additives, chemical mechanical grinding is performed in an acidic environment, and the problem of insufficient milling selection ratio of oxides compared with silicon-containing materials is solved, and the grinding efficiency is improved. Simplified process flow.
Patent Information
- Application Number
- CN202011306706.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-20
- Filing Date
- 2020-11-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-11-20
AI Technical Summary
The existing abrasive compositions are difficult to improve the grinding selection ratio of oxides to silicon-containing materials, resulting in low efficiency in chemical mechanical grinding process and increasing production costs and time.
Using a grinding composition containing low silanol-based density silica particles and specific structural additives, grinding is carried out under an acidic pH environment, and using additive molecules to form a protective layer on the surface of the abrasive particles and silicon-containing materials to increase the removal rate of oxides. And reduce the grinding speed of silicon-containing materials.
A high grinding selection ratio of oxides to silicon-containing materials is achieved, simplifying process flow, reducing production costs and time, and without the need to form an additional grinding stop layer.
Smart Images

Figure CN112824475B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polishing composition, a polishing method using the polishing composition, and a method for producing a substrate. Background Art
[0002] In the semiconductor industry, planarization technology is usually used to improve the flatness of the surface of a semiconductor substrate (such as a wafer). Chemical mechanical polishing (CMP) is a commonly used planarization technology. Chemical mechanical polishing technology includes a method of planarizing the surface of a polishing object (polished object) such as a semiconductor substrate using a polishing composition, wherein the polishing composition contains abrasive particles such as silicon dioxide, aluminum oxide, or ceria, an anticorrosive agent, a surfactant, etc.
[0003] Furthermore, substrates made of semiconductor materials such as silicon or silicon germanium (sometimes referred to as "silicon-containing materials" in this specification) have become popular. Therefore, the demand for polishing compositions used for polishing substrates made of silicon-containing materials has also increased.
[0004] Patent Document 1 discloses a chemical mechanical polishing composition comprising (A) inorganic particles, organic particles, or a mixture or a composite thereof, (B) at least one oxidizing agent, and (C) an aqueous medium. The chemical mechanical polishing composition of Patent Document 1 can be used for chemical mechanical polishing of elemental germanium or silicon germanium.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Taiwan Patent Application No. 201311842A1 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] As semiconductor devices become increasingly miniaturized, the requirements for the chemical mechanical polishing process have become increasingly stringent. For example, in semiconductor devices, a shallow trench isolation (STI) structure formed by an oxide (e.g., silicon oxide) is often used to separate semiconductor elements from each other. In the shallow trench isolation process, chemical mechanical polishing can be performed to remove excess oxide material formed on the substrate. In order to stop the chemical mechanical polishing, a polishing stop layer with a lower polishing speed is usually formed between the oxide layer and the substrate. In addition, in order to stop the chemical mechanical polishing at a desired position with high precision, it is necessary to increase the polishing selectivity of the oxide layer relative to the polishing stop layer. Materials commonly used in the polishing stop layer may include nitrides, carbides, or carbonitrides, such as silicon nitride.
[0010] When an oxide layer is formed on a substrate formed of a silicon-containing material (e.g., a silicon germanium substrate or a silicon substrate), as long as the grinding selectivity of the oxide relative to the substrate material can be improved, a grinding stop layer (e.g., a silicon nitride layer) may not be further formed. In this way, the complexity of the process can be simplified, and the time and cost required for production can be reduced. In addition, as long as the grinding speed of the oxide can be increased (sometimes "grinding speed" is referred to as "removal speed" in this specification), the time required for the grinding process can be greatly shortened, and the production efficiency of the product can be improved.
[0011] However, it is still difficult to increase the polishing selectivity (sometimes referred to as "polishing rate ratio" or "removal rate ratio" in this specification) of oxides to silicon-containing materials (such as silicon germanium or silicon) to a sufficient degree in existing polishing compositions. In other words, it is still difficult to use silicon germanium or silicon as a polishing stop layer when chemically mechanically polishing oxides.
[0012] The present invention is made in view of the above actual situation, and aims to provide a polishing composition having an improved polishing rate ratio of oxides relative to silicon germanium or silicon. Furthermore, the polishing composition provided by the present invention can also improve the polishing rate of oxides. In addition, the present invention also provides a polishing method using the polishing composition and a method for manufacturing a substrate.
[0013] Solutions for solving problems
[0014] In order to achieve the above-mentioned objectives, some embodiments of the present invention provide the following polishing compositions, polishing methods using the polishing compositions, and methods for producing substrates.
[0015] [1] A polishing composition comprising: polishing abrasive grains comprising silica particles, wherein the density of silanol groups on the surface of the silica particles is 0 to 3.0 per nm 2, the silanol group density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration; an additive molecule; a pH adjuster for adjusting the pH of the polishing composition to a range of 1.5 to 4.5; and a dispersion medium. The additive molecule has a structure represented by formula (I).
[0016]
[0017] In formula (I), R 1 and R 2 are independently H, C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 A straight-chain alkenyl group; n is an integer of 2 to 40; and m, p and q are each independently 0 or 1, r is an integer of 0 to 2, when m is 1, R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight-chain alkenyl, when p is 1, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl.
[0018] [2] The polishing composition according to [1], wherein the content of the additive molecules is 50 to 10,000 ppm by weight relative to the total weight of the polishing composition.
[0019] [3] The polishing composition according to [1] or [2], wherein the weight average molecular weight of the additive molecule is 100 to 10,000.
[0020] [4] The polishing composition according to any one of [1] to [3], wherein in the formula (I), R 1 For H, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 A straight-chain alkenyl group; n is an integer of 2 to 20; and m, p, q and r are all 0.
[0021] [5] The polishing composition according to any one of [1] to [3], wherein in the formula (I), R 1 and R 2 are both H; n is an integer from 2 to 40; and m and p are both 0, and q and r are both 1.
[0022] [6] The polishing composition according to any one of [1] to [3], wherein in the formula (I), R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2 is H; n is an integer from 2 to 20; and m and p are both 0, and q and r are both 1.
[0023] [7] The polishing composition according to any one of [1] to [3], wherein in the formula (I), R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2 is H; n is an integer from 2 to 20; and m, q and r are all 1, and p is 0.
[0024] [8] The polishing composition according to any one of [1] to [3], wherein in the formula (I), R 1 and R 2 are all H; n is an integer from 2 to 20; and m, p and q are all 0, and r is 2.
[0025] [9] The polishing composition according to any one of [1] to [8], wherein the content of the polishing abrasive grains is 0.1 to 10% by weight relative to the total weight of the polishing composition.
[0026]
[10] A polishing method comprising the step of polishing an object to be polished using the polishing composition described in any one of [1] to [9], wherein the material of the object to be polished comprises a silicon-containing material and an oxide, wherein the silicon-containing material is Si x Ge 1-x Indicates, and x=0.1~1.
[0027]
[11] The polishing method according to
[10] , wherein, when the polishing pressure is 1.0 psi, the removal rate of the oxide by the polishing composition is a first removal rate R1, the removal rate of the silicon-containing material by the polishing composition is a second removal rate R2, and the ratio of the first removal rate to the second removal rate R1 / R2 is greater than 10.
[0028]
[12] A method for manufacturing a substrate, comprising: preparing a substrate, wherein the surface of the substrate comprises a silicon-containing material and an oxide, wherein the silicon-containing material is Si x Ge 1-xwherein x=0.1 to 1; and a step of polishing the substrate using the polishing composition described in any one of [1] to [9].
[0029] Effects of the Invention
[0030] The grinding composition of the present invention comprises grinding abrasives that meet specific conditions and additives with specific structures, and under specific pH environment, a high grinding selectivity ratio of oxides relative to silicon-containing materials can be achieved. In more detail, the grinding composition of the present invention uses grinding abrasives with low silanol group density, so the grinding speed of oxides can be increased. In addition, the grinding composition of the present invention uses additive molecules with a specific structure (i.e., a structure shown in formula (I) described later), so the grinding speed of silicon-containing (e.g., silicon germanium or silicon) materials can be reduced. Furthermore, the grinding composition of the present invention is used under a specific acidic pH (i.e., pH is above 1.5 and below 4.5) environment, so the removal speed of oxides and the reduction of the grinding selectivity ratio of oxides relative to silicon-containing materials can be avoided. When the grinding composition of the present invention is used to chemically mechanically grind the oxide layer formed on the silicon-containing material layer, the silicon-containing material layer can be directly used as a grinding stop layer, so there is no need to further form a grinding stop layer (e.g., a silicon nitride layer). Thus, the complexity of the process can be simplified, and the time and cost required for production can be reduced. In addition, for the grinding composition of the present invention, the removal speed of oxides can be adjusted by adjusting the type and content of the additive. For example, the oxide removal rate can be further increased, thereby shortening the time required for the polishing process. DETAILED DESCRIPTION
[0031] In order to make the above and other objects, features, and advantages of the present invention more clear and easier to understand, preferred embodiments are given below and described in detail.
[0032] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.
[0033] One embodiment of the present invention provides a polishing composition, comprising: polishing abrasive particles comprising silica particles, wherein the silanol group density on the surface of the silica particles is 0 to 3.0 per nm. 2 , the silanol group density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration; an additive molecule; a pH adjuster for adjusting the pH of the polishing composition to a range of 1.5 to 4.5; and a dispersion medium. The additive molecule has a structure represented by formula (I).
[0034]
[0035] In formula (I), R1 and R 2 are independently H, C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 A straight-chain alkenyl group; n is an integer of 2 to 40; and m, p and q are each independently 0 or 1, r is an integer of 0 to 2, when m is 1, R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight-chain alkenyl, when p is 1, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl.
[0036] In the present embodiment, for the grinding composition, the silicon dioxide particles with lower silanol group density are used as grinding abrasive grains, and the additive with specific structure is combined, and under a specific pH environment, the high grinding selectivity ratio of oxide relative to silicon germanium or silicon can be achieved (that is, the grinding selectivity ratio of oxide / silicon-containing material is high). When the grinding composition of the present embodiment is used, when the grinding object comprising silicon-containing material and oxide is subjected to chemical mechanical grinding, the removal rate of oxide can be increased, and the grinding selectivity ratio of oxide relative to silicon germanium or silicon can be increased. Therefore, the silicon-containing material can be used as a grinding stop layer, and there is no need to further form a grinding stop layer. Thus, the surface flatness of the grinding object becomes good, the complexity of the process can be simplified, and the time and cost required for production can be reduced.
[0037] There is no particular limitation on the polishing object suitable for the polishing composition of the present invention, as long as it is a common semiconductor substrate. The polishing composition of the present invention is particularly suitable for polishing substrates whose surfaces contain silicon-containing materials and oxides, so as to give full play to the technical effects of the present invention. As a specific example of oxides, silicon oxide can be cited. Silicon-containing materials can include, for example, amorphous silicon, single crystal silicon, polycrystalline silicon, silicon germanium, or a combination of these. As a specific example of silicon-containing materials, for example, molecular formula Si x Ge 1-x The silicon-containing material shown. The value of x in the above molecular formula is preferably 0.1 or more, more preferably 0.2 or more, and further preferably 0.3 or more. The value of x in the above molecular formula is preferably 1 or less, more preferably 0.9 or less, and further preferably 0.8 or less.
[0038] Furthermore, in this specification, as long as the substrate containing silicon-containing materials and oxides contains silicon-containing materials and oxides on the surface of the substrate, its form is not particularly limited. For example, it can be a substrate having a patterned structure formed by oxides and silicon-containing materials on the surface of any substrate, and it can also be a substrate having an oxide layer on a substrate composed of silicon-containing materials, and it can also be a substrate having a patterned structure formed by an oxide layer and other materials on a substrate (or silicon-containing material layer) composed of silicon-containing materials. Several different forms of "substrates containing silicon-containing materials and oxides" are listed here, but these are not intended to limit the present invention. The present invention may include any other possible forms of "substrates containing silicon-containing materials and oxides".
[0039] The various components contained in the polishing composition of this embodiment are described below.
[0040] [Grinding abrasive]
[0041] The grinding composition of this embodiment contains silica as grinding abrasive. In some embodiments of the present invention, the grinding abrasive is colloidal silica. In some embodiments of the present invention, silica particles with a low silanol group density are used as grinding abrasive. In this specification, "silanol group density" refers to the number of silanol groups per unit area on the surface of silica particles. The silanol group density is an indicator used to represent the electrical or chemical properties of the surface of silica particles.
[0042] In this specification, the silanol group density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration. For example, the average silanol group density (unit: pcs / nm) on the surface of silica (abrasive grains) can be calculated by using the Sears titration method using neutralization titration described in "Analytical Chemistry, vol. 28, No. 12, 1956, 1982-1983" by GW Sears. 2 ). The "Sears titration method" is an analytical method commonly used by colloidal silica manufacturers to evaluate the silanol group density. It is a method based on the amount of sodium hydroxide aqueous solution required to change the pH from 4 to 9. The details of the silanol group density measurement are described in detail in the following examples.
[0043] The silanol group density of the polishing abrasive is 0 to 3.0 per nm. 2. When the silanol group density is within the above range, the silica particles can better adsorb the additive molecules in the present embodiment. Thereby, the additive molecules can be adsorbed and concentrated on the surface of the grinding abrasive, and the aggregation of the grinding abrasive caused by the steric hindrance of the additive molecules can be avoided. Therefore, the dispersion stability of the grinding abrasive in the grinding composition becomes good, the grinding abrasive becomes difficult to aggregate, and the storage stability also becomes good. In addition, on the other hand, by adsorbing and concentrating the additive molecules on the surface of the grinding abrasive, the grinding selectivity of the oxide relative to silicon germanium or silicon can be improved. The silanol group density of the grinding abrasive is preferably greater than 0 / nm 2 , more preferably 0.5 / nm 2 More preferably, 1.0 / nm 2 More preferably, 1.2 / nm 2 In addition, the silanol group density of the polishing abrasive is preferably 2.5 / nm 2 Below, more preferably 2.0 pieces / nm 2 Below, more preferably 1.8 / nm 2 the following.
[0044] In one embodiment of the present invention, in order to make the number of silanol groups per unit surface area of the abrasive grains 0 to 3.0 / nm 2 , can be controlled by selecting a method for manufacturing the abrasive, for example, a heat treatment such as sintering is appropriate. In one embodiment of the present invention, sintering is performed by, for example, maintaining the abrasive (e.g., silicon dioxide) at 120 to 200°C for more than 30 minutes. By performing such a heat treatment, the number of silanol groups on the surface of the abrasive can be 0 to 3.0 / nm. 2 Unless such special treatment is performed, the number of silanol groups on the abrasive surface will not become 0 / nm. 2 Above and 3.0 / nm 2 the following.
[0045] The average primary particle size of the grinding abrasive is preferably more than 5nm, more preferably more than 7nm, further preferably more than 10nm, and particularly preferably more than 25nm. As the average primary particle size of the grinding abrasive becomes larger, the grinding speed of silicon-containing materials and oxides can be further improved. The average primary particle size of the grinding abrasive is preferably less than 120nm, more preferably less than 80nm, and further preferably less than 50nm. As the average primary particle size of the grinding abrasive becomes smaller, when the grinding object is ground using the grinding composition, a grinding surface with fewer scratches can be easily obtained. In addition, the value of the average primary particle size of the grinding abrasive can be calculated based on the specific surface area measured using the BET method.
[0046] The average secondary particle size of the grinding abrasive is preferably more than 10nm, more preferably more than 20nm, further preferably more than 30nm, and particularly preferably more than 50nm. As the average secondary particle size of the grinding abrasive becomes larger, the grinding speed of silicon-containing materials and oxides can be further improved. The average secondary particle size of the grinding abrasive is preferably less than 250nm, more preferably less than 200nm, further preferably less than 150nm, and particularly preferably less than 100nm. As the average secondary particle size of the grinding abrasive becomes smaller, when the grinding object is ground using the grinding composition, a grinding surface with fewer scratches can be easily obtained. In addition, the value of the average secondary particle size of the grinding abrasive can be measured, for example, by laser scattering method.
[0047] In some embodiments of the present invention, the zeta potential of the grinding abrasive under acidic conditions is positive, so the grinding abrasive can be strongly repelled from each other and well dispersed. Therefore, the storage stability of the grinding composition is improved. Furthermore, in some embodiments of the present invention, the surface zeta potential of the grinding abrasive is positive, and there is an electrostatic attraction between the negatively charged grinding object (such as an oxide), so the grinding speed of the oxide can be increased. In some embodiments of the present invention, the zeta potential of the grinding abrasive under specific acidic conditions (such as a pH of 1.5 or more and 4.5 or less) is preferably above +10mV, more preferably above +20mV, and further preferably above +30mV. In addition, the zeta potential of the grinding abrasive under specific acidic conditions (such as a pH of 1.5 or more and 4.5 or less) is preferably below +100mV, more preferably below +80mV; more preferably below +60mV, and particularly preferably below +40mV.
[0048] In some embodiments of the present invention, the content of the grinding abrasive is preferably 0.01% by weight or more, more preferably 0.05% by weight or more, more preferably 0.1% by weight or more, and particularly preferably 0.3% by weight or more, relative to the total weight of the grinding composition. In addition, the content of the grinding abrasive is preferably 10.0% by weight or less, more preferably 5.0% by weight or less, further preferably 2.0% by weight or less, and particularly preferably 1.0% by weight or less. As the content of the grinding abrasive increases, the grinding speed of the grinding object increases. On the other hand, the less the content of the grinding abrasive becomes, the aggregation of the grinding abrasive also becomes difficult to occur in addition to reducing the material cost of the grinding composition. Furthermore, by reducing the content of the grinding abrasive, the surface of the grinding object after grinding caused by excessive grinding can also be avoided from becoming uneven.
[0049] [Additive molecules]
[0050] The polishing composition of this embodiment comprises at least one additive molecule, and the additive molecule has a structure represented by formula (I):
[0051]
[0052] In formula (I), R 1 and R 2 are independently H, C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 A straight-chain alkenyl group; n is an integer of 2 to 40; and m, p and q are each independently 0 or 1, r is an integer of 0 to 2, when m is 1, R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight-chain alkenyl, when p is 1, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 In one embodiment, when m is 1, R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 When p is 1, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl.
[0053] Here, in this specification, C1 to C 18 A straight-chain alkyl group (i.e., a straight-chain alkyl group having 1 to 18 carbon atoms) or a C3 to C 18 The branched alkyl group (i.e., a branched alkyl group having 3 to 18 carbon atoms) is not particularly limited, and examples thereof include n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, 2-methylbutyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, tert-pentyl, hexyl, isohexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl (lauryl), 2-ethylhexyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, and the like.
[0054] In this manual, C2 to C 18 The straight-chain alkenyl group (a straight-chain alkenyl group having 2 to 20 carbon atoms) is not particularly limited, and examples thereof include vinyl, propenyl, allyl, isopropenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 1-heptenyl, 2-heptenyl, 3-heptenyl, 9-decenyl, 11-dodecenyl, (Z)-9-pentadecenyl, and oleyl (Z-9-octadecenyl).
[0055] As mentioned above, the silanol group density on the surface of silicon dioxide grinding abrasive grains is low, so the hydrophobicity of grinding abrasive grains is improved. In addition, the surface of the silicon-containing material (such as silicon germanium or silicon) as the grinding object is also a surface with higher hydrophobicity. When not using the above-mentioned additive, the affinity between the hydrophobic grinding abrasive grains and the hydrophobic silicon-containing material is large, so the grinding speed of the grinding abrasive grains to the silicon-containing material is high. In the case described, the grinding speed ratio of the oxide relative to the silicon-containing material becomes too low, so the silicon-containing material cannot be used as the grinding stop layer when the oxide is ground.
[0056] Referring to the structure shown in the above formula (I), the additive molecule has a hydrophobic molecular segment, such as R 1 , R 2 Or an alkyl segment on the main chain. The additive molecules are adsorbed on the hydrophobic surface of the grinding abrasive and the silicon-containing material with the help of hydrophobic molecular segments and concentrated. Therefore, a thin layer formed by the additive molecules is adsorbed on the surface of the grinding abrasive and the silicon-containing material. Due to the three-dimensional structure of the additive molecules, hindrance occurs, thereby reducing or avoiding the direct contact between the grinding abrasive and the silicon-containing material. In other words, the additive molecules can form a structure similar to a protective layer on the surface of the silicon-containing material, thereby greatly reducing the grinding speed of the silicon-containing material. As a result, the grinding speed ratio of the oxide to the silicon-containing material is increased, so the silicon-containing material can be used as a grinding stop layer during oxide grinding.
[0057] In addition, refer to the structure shown in the above formula (I). The additive molecule has a hydrophilic group at the terminal position, such as a hydroxyl group (-OH). Therefore, after the additive molecule is adsorbed on the surface of the grinding abrasive, the hydrophilic groups on the surface of the grinding abrasive increase, and the hydrophilicity of the grinding abrasive also increases. Furthermore, the surface of the oxide of the grinding object is also a surface with high hydrophilicity. Although a thin layer formed by the additive molecules is adsorbed on the surface of the grinding abrasive, in addition to the strong affinity between the hydrophilic grinding abrasive and the hydrophilic oxide, the grinding abrasive and the oxide also have an electrostatic attraction, so the grinding speed of the oxide can still be moderately increased. As a result, the grinding speed ratio of the oxide relative to the silicon-containing material is further improved, so it becomes more conducive to using the silicon-containing material as a grinding stop layer when grinding the oxide. In addition, the increase in the grinding speed of the oxide is also related to the shortening of the time spent in the grinding process, which helps to improve production efficiency.
[0058] In some embodiments of the present invention, in the structure shown in formula (I), R 1 For H, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18Straight-chain alkenyl group; n is an integer of 2 to 20; and m, p, q and r are all 0. In this embodiment, the molecular structure of the additive molecule is relatively simple and can be easily arranged closely. Therefore, the additive molecule can easily form a thin layer with a relatively dense structure on the surface of the grinding abrasive and the silicon-containing material, and can well protect the silicon-containing material. Therefore, the grinding speed of the silicon-containing material can be greatly reduced. Furthermore, in this embodiment, the additive molecule has a large number of hydrophilic groups, so the hydrophilicity of the surface of the grinding abrasive can be improved. Therefore, the affinity between the grinding abrasive and the hydrophilic oxide is improved, and the grinding speed of the oxide is further improved. As a result, the grinding speed ratio of the oxide to the silicon-containing material is further improved, which makes it more advantageous to use the silicon-containing material as a grinding stop layer when grinding the oxide, and is also beneficial to shortening the time spent in the grinding process.
[0059] In this embodiment, R 2 Preferred C1~C 18 Straight chain alkyl, more preferably C1-C 10 The linear alkyl group is more preferably a C1 to C5 linear alkyl group, and even more preferably a C1 to C3 linear alkyl group.
[0060] In some embodiments of the present invention, in the structure shown in formula (I), R 1 and R 2 are all H; n is an integer of 2 to 40; and m and p are both 0, and q and r are both 1. In this embodiment, the molecular structure of the additive molecules is relatively simple and easy to arrange tightly. Therefore, the additive molecules can easily form a thin layer with a relatively dense structure on the surface of the grinding abrasive and the silicon-containing material, and can well protect the silicon-containing material. Therefore, the grinding speed of the silicon-containing material can be greatly reduced. Furthermore, in this embodiment, the additive molecules have a large number of hydrophilic groups, so the hydrophilicity of the surface of the grinding abrasive can be improved. Therefore, the affinity between the grinding abrasive and the hydrophilic oxide is improved, and the grinding speed of the oxide is further improved. As a result, the grinding speed ratio of the oxide to the silicon-containing material is further improved, which makes it more conducive to using the silicon-containing material as a grinding stop layer when grinding the oxide, and is also conducive to shortening the time spent in the grinding process.
[0061] In some embodiments of the present invention, in the structure shown in formula (I), R 1 and R 2is H; and m, p and q are all 0, and r is 2. In this embodiment, the molecular structure of the additive molecule is relatively simple and easy to arrange tightly. Therefore, the additive molecule can easily form a thin layer with a relatively dense structure on the surface of the grinding abrasive and the silicon-containing material, and can well protect the silicon-containing material. Therefore, the grinding speed of the silicon-containing material can be greatly reduced. Furthermore, in this embodiment, the additive molecule has a large number of hydrophilic groups, so the hydrophilicity of the surface of the grinding abrasive can be improved. Therefore, the affinity between the grinding abrasive and the hydrophilic oxide is improved, and the grinding speed of the oxide is further improved. As a result, the grinding speed ratio of the oxide relative to the silicon-containing material is further improved, which makes it more conducive to using the silicon-containing material as a grinding stop layer when grinding the oxide, and is also conducive to shortening the time spent in the grinding process.
[0062] In some embodiments of the present invention, in the structure shown in formula (I), R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2 is H; n is an integer of 2 to 20; and m and p are both 0, and q and r are both 1. In this embodiment, the additive molecule has a hydrophobic molecular segment (i.e., an alkyl segment at the end). Therefore, the additive molecule becomes more easily adsorbed on the hydrophobic surfaces of the grinding abrasive and the silicon-containing material. Furthermore, the hydrophobic molecular segment can make the three-dimensional structure of the additive molecule larger, thereby becoming beneficial to further reduce or avoid direct contact between the grinding abrasive and the silicon-containing material. As a result, the grinding speed of the silicon-containing material is further reduced, and the grinding speed ratio of the oxide relative to the silicon-containing material is further increased, thereby becoming more beneficial to use the silicon-containing material as a grinding stop layer when grinding the oxide.
[0063] In this embodiment, R 1 Preferred C3~C 18 Straight chain alkyl or C2~C 18 Straight chain alkenyl, more preferably C5 to C 18 Straight chain alkyl or C5~C 18 Straight chain alkenyl, more preferably C 10 ~C 18 Straight chain alkyl or C 10 ~C 18 Straight chain alkenyl, more preferably C 10 ~C 16 Straight chain alkyl or C 12 ~C 18 Straight chain alkenyl, particularly preferably C 10 ~C 14 Straight chain alkyl.
[0064] In some embodiments of the present invention, in the structure shown in formula (I), R 1 For H, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight-chain alkenyl group; n is an integer of 2 to 20; and m and p are both 0, and q and r are both 1. In this embodiment, the additive molecule has a large number of hydrophobic molecular segments (i.e., alkyl segments located in the side chains). Therefore, the additive molecule becomes more easily adsorbed on the hydrophobic surfaces of the grinding abrasive and the silicon-containing material. Furthermore, a large number of hydrophobic molecular segments can make the three-dimensional structure of the additive molecule larger, so it becomes beneficial to further reduce or avoid direct contact between the grinding abrasive and the silicon-containing material. As a result, the grinding speed of the silicon-containing material is further reduced, and the grinding speed ratio of the oxide relative to the silicon-containing material is further increased, so it becomes more beneficial to use the silicon-containing material as a grinding stop layer when grinding the oxide.
[0065] In this embodiment, R 2 Preferred C3~C 18 Straight chain alkyl or C2~C 18 Straight chain alkenyl, more preferably C5 to C 18 Straight chain alkyl or C5~C 18 Straight chain alkenyl, more preferably C 10 ~C 18 Straight chain alkyl or C 10 ~C 18 Straight chain alkenyl, more preferably C 10 ~C 16 Straight chain alkyl or C 12 ~C 18 Straight chain alkenyl, particularly preferably C 10 ~C 14 Straight chain alkyl.
[0066] In some embodiments of the present invention, in the structure shown in formula (I), R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2is H; n is an integer of 2 to 20; and m, q and r are all 1, and p is 0. In this embodiment, the additive molecule has a hydrophobic molecular segment (i.e., an alkyl segment at the end). Therefore, the additive molecule becomes more easily adsorbed on the hydrophobic surfaces of the grinding abrasive and the silicon-containing material. Furthermore, the hydrophobic molecular segment can make the three-dimensional structure of the additive molecule larger, thereby becoming beneficial to further reduce or avoid direct contact between the grinding abrasive and the silicon-containing material. As a result, the grinding speed of the silicon-containing material is further reduced, and the grinding speed ratio of the oxide relative to the silicon-containing material is further increased, thereby becoming more beneficial to use the silicon-containing material as a grinding stop layer when grinding the oxide.
[0067] In this embodiment, R 1 Preferred C3~C 18 Straight chain alkyl or C2~C 18 Straight chain alkenyl, more preferably C5 to C 18 Straight chain alkyl or C5~C 18 Straight chain alkenyl, more preferably C 10 ~C 18 Straight chain alkyl or C 10 ~C 18 Straight chain alkenyl, more preferably C 10 ~C 16 Straight chain alkyl or C 12 ~C 18 Straight chain alkenyl, particularly preferably C 10 ~C 14 Straight chain alkyl.
[0068] In some embodiments of the present invention, in the structure shown in formula (I), R 1 For H, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight-chain alkenyl group; n is an integer of 2 to 20; and m is 0, and p, q and r are all 1. In this embodiment, the additive molecule has a large number of hydrophobic molecular segments (i.e., alkyl segments located in the side chains). Therefore, the additive molecule becomes more easily adsorbed on the hydrophobic surfaces of the grinding abrasive and the silicon-containing material. Furthermore, a large number of hydrophobic molecular segments can make the three-dimensional structure of the additive molecule larger, so it becomes beneficial to further reduce or avoid direct contact between the grinding abrasive and the silicon-containing material. As a result, the grinding speed of the silicon-containing material is further reduced, and the grinding speed ratio of the oxide relative to the silicon-containing material is further increased, so it becomes more beneficial to use the silicon-containing material as a grinding stop layer when grinding the oxide.
[0069] In this embodiment, R 2 Preferred C3~C18 Straight chain alkyl or C2~C 18 Straight chain alkenyl, more preferably C5 to C 18 Straight chain alkyl or C5~C 18 Straight chain alkenyl, more preferably C 10 ~C 18 Straight chain alkyl or C 10 ~C 18 Straight chain alkenyl, more preferably C 10 ~C 16 Straight chain alkyl or C 12 ~C 18 Straight chain alkenyl, particularly preferably C 10 ~C 14 Straight chain alkyl.
[0070] In some embodiments of the present invention, the weight average molecular weight (MW) of the additive molecule is preferably 100 or more, more preferably 200 or more, and further preferably 300 or more. In addition, the weight average molecular weight (MW) of the additive molecule is preferably 10000 or less, more preferably 6000 or less, and further preferably 4000 or less. The weight average molecular weight in this specification is measured by gel permeation chromatography (GPC) using polystyrene as a standard substance.
[0071] In some embodiments of the present invention, the weight average molecular weight (MW) of the additive molecules is 100 or more, 200 or more, 250 or more, 300 or more, 450 or more, 400 or more, 500 or more, or 600 or more. In addition, in some embodiments of the present invention, the weight average molecular weight (MW) of the additive molecules is 1500 or less, 1000 or less, 950 or less, 900 or less, 800 or less, 700 or less, 650 or less, or 600 or less.
[0072] In some embodiments of the present invention, in formula (I), R 1 For H, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 A straight-chain alkenyl group; n is an integer of 2 to 20; and when m, p, q and r are all 0, the weight average molecular weight (MW) of the additive molecule is 100 or more, 200 or more, 250 or more, 300 or more, or 400 or more. In some embodiments of the present invention, in formula (I), R 1 For H, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18A straight-chain alkenyl group; n is an integer of 2 to 20; and when m, p, q and r are all 0, the weight average molecular weight (MW) of the additive molecule is 1000 or less, 950 or less, 900 or less, 800 or less, 700 or less, 600 or less, or 500 or less.
[0073] In some embodiments of the present invention, in formula (I), R 1 and R 2 are all H; n is an integer of 2 to 40; and when m and p are both 0, q and r are both 1, the weight average molecular weight (MW) of the additive molecule is 100 or more, 150 or more, 200 or more, 250 or more, 280 or more, 300 or more, 400 or more, 500 or more, 600 or more, or 700 or more. In some embodiments of the present invention, in formula (I), R 1 and R 2 are all H; n is an integer of 2 to 40; and when m and p are both 0, q and r are both 1, the weight average molecular weight (MW) of the additive molecule is less than 3000, less than 1500, less than 1000, less than 900, or less than 800.
[0074] In some embodiments of the present invention, when an alkyl ether is used as a hydrophobic molecular segment, that is, in formula (I), (i) R 1 For H, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 straight-chain alkenyl; n is an integer of 2 to 20; and m and p are both 0, q and r are both 1, and (ii) R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2 When m and p are both 0, q and r are both 1, the weight average molecular weight (MW) of the additive molecule is 100 or more, 200 or more, 250 or more, 300 or more, 350 or more, or 400 or more. In addition, in some embodiments of the present invention, when the alkyl ether is used as the hydrophobic molecular segment, the weight average molecular weight (MW) of the additive molecule is 1500 or less, 1000 or less, 900 or less, 800 or less, 600 or less, or 500 or less.
[0075] In some embodiments of the present invention, when a fatty acid ester is used as a hydrophobic molecular segment, that is, in formula (I), (i) R 1 For H, R 2 C1~C 18 Straight chain alkyl, C3~C 18Branched alkyl or C2~C 18 straight-chain alkenyl; n is an integer of 2 to 20; and m is 0, p, q and r are all 1, and (ii) R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2 is H; n is an integer of 2 to 20; and m, q and r are all 1, and p is 0, the weight average molecular weight (MW) of the additive molecule is 100 or more, 200 or more, 250 or more, 300 or more, 350 or more, or 400 or more. In addition, in some embodiments of the present invention, when the fatty acid ester is used as the hydrophobic molecular segment, the weight average molecular weight (MW) of the additive molecule is 1500 or less, 1000 or less, 900 or less, 800 or less, 700 or less, or 600 or less.
[0076] In some embodiments of the present invention, in formula (I), R 1 and R 2 are all H; n is an integer of 2 to 20; and m, p and q are all 0, and when r is 2, the weight average molecular weight (MW) of the additive molecule is 100 or more, 150 or more, 200 or more, 220 or more, or 230 or more. In some embodiments of the present invention, in formula (I), R 1 and R 2 are all H; n is an integer of 2 to 20; and m, p and q are all 0, and when r is 2, the weight average molecular weight (MW) of the additive molecule is less than 1000, less than 800, less than 600, less than 500, or less than 400.
[0077] When the weight average molecular weight of the additive molecule is too large, the three-dimensional structure of the additive molecule is likely to become too large. In the case described above, gaps are easily formed between the additive molecules adsorbed on the grinding abrasive and the silicon-containing material, and it is difficult to form a densely structured thin layer on the surface of the grinding abrasive and the silicon-containing material. As a result, the additive molecules cannot protect the silicon-containing material well and cannot fully reduce the grinding speed of the silicon-containing material. Therefore, it is impossible to increase the grinding speed ratio of the oxide relative to the silicon-containing material, which is not conducive to using the silicon-containing material as a grinding stop layer when grinding the oxide.
[0078] On the other hand, when the weight average molecular weight of the additive molecule is too small, the hydrophobic segments of the additive molecule may become too few, and the hydrophilicity of the additive molecule may become too high. In the above case, it becomes difficult for the additive molecule to be adsorbed on the surface of the grinding abrasive and the silicon-containing material. Therefore, the additive molecule cannot protect the silicon-containing material well, and the grinding speed of the silicon-containing material cannot be sufficiently reduced. Furthermore, when the hydrophilicity of the additive molecule becomes too high, a thin layer formed by the additive molecule may be adsorbed on the hydrophilic oxide surface, thereby reducing the grinding speed of the oxide. Therefore, the grinding speed ratio of the oxide to the silicon-containing material becomes lower, which becomes unfavorable for using the silicon-containing material as a grinding stop layer when grinding the oxide.
[0079] It should be noted that the weight average molecular weight of the additive molecule can be a value measured by GPC method (water system, polyethylene oxide conversion). The weight average molecular weight can be obtained by polyethylene glycol conversion by gel permeation chromatography (GPC) using a GPC device (model: Prominence + ELSD detector (ELSD-LTII) manufactured by Shimadzu Corporation).
[0080] The additive molecule may be a commercial product or a synthesized product. In the case of synthesis, the production method is not particularly limited, and a known production method can be used.
[0081] In some embodiments of the present invention, the content of the additive molecules is preferably 10 wtppm or more, more preferably 30 wtppm or more, further preferably 50 wtppm or more, and particularly preferably 70 wtppm or more, relative to the total weight of the polishing composition. In addition, the content of the additive molecules is preferably 10000 wtppm or less, more preferably 5000 wtppm or less, preferably 2000 wtppm or less, and particularly preferably 1000 wtppm or less.
[0082] In some embodiments of the present invention, the content of the additive molecules relative to the total weight of the polishing composition is 60 ppm or more, 80 ppm by weight or more, 90 ppm by weight or more, 95 ppm by weight or more, 120 ppm by weight or more, 150 ppm by weight or more, or 200 ppm by weight or more. In some embodiments of the present invention, the content of the additive molecules relative to the total weight of the polishing composition is 900 ppm by weight or less, 700 ppm by weight or less, 500 ppm by weight or less, 400 ppm by weight or less, 350 ppm by weight or less, or 300 ppm by weight or less.
[0083] When the content of the additive molecules in the polishing composition is too much, there is a possibility that too many additive molecules are adsorbed on the surface of the polishing abrasive and the silicon-containing material. In addition, when the content of the additive molecules is too much, the additive molecules may also form a thin layer on the surface of the oxide. As a result, the polishing speed of the silicon-containing material and the polishing speed of the oxide are both reduced, and the polishing speed ratio of the oxide to the silicon-containing material cannot be fully improved. Therefore, it is not conducive to using the silicon-containing material as a polishing stop layer when polishing the oxide, and it is also disadvantageous in shortening the time spent in the polishing process.
[0084] On the other hand, when the content of the additive molecules in the grinding composition is too little, it is difficult for the additive molecules to form a thin layer on the surface of the grinding abrasive and the silicon-containing material, and it is particularly difficult to cover the entire surface of the grinding abrasive and the silicon-containing material. Therefore, the additive molecules cannot protect the silicon-containing material well, and it becomes impossible to fully reduce the grinding speed of the silicon-containing material. In addition, when the content of the additive molecules is too little, the hydrophilicity of the grinding abrasive becomes insufficient, and it becomes difficult to effectively improve the affinity between the grinding abrasive and the hydrophilic oxide, and therefore the grinding speed of the oxide cannot be increased. As mentioned above, when the content of the additive molecules is too little, it is difficult to increase the grinding speed ratio of the oxide relative to the silicon-containing material. Therefore, it becomes unfavorable to use the silicon-containing material as a grinding stop layer when grinding the oxide.
[0085] [pH adjuster]
[0086] The polishing composition of this embodiment contains a pH adjuster. The pH value of the polishing composition can be adjusted to a range of 1.5 to 4.5 by the pH adjuster. As the pH adjuster, a known acid or base can be used.
[0087] The acid of the pH adjusting agent used in the polishing composition of the present embodiment can be either an inorganic acid or an organic acid, and can also be a chelating agent. As a specific example of an inorganic acid that can be used as a pH adjusting agent, for example, hydrochloric acid (HCl), sulfuric acid (H2SO4), nitric acid (HNO3), hydrofluoric acid (HF), boric acid (H3BO3), carbonic acid (H2CO3), hypophosphorous acid (H3PO2), phosphorous acid (H3PO3) and phosphoric acid (H3PO4) can be cited. Among these inorganic acids, hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid are preferred.
[0088] Specific examples of organic acids that can be used as pH adjusters include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylvaleric acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, hydroxyacetic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, lactic acid, glyoxylic acid, 2-furancarboxylic acid, Acid, 2,5-furandicarboxylic acid, 3-furancarboxylic acid, 2-tetrahydrofuran carboxylic acid, methoxyacetic acid, methoxyphenylacetic acid, and phenoxyacetic acid. Organic sulfuric acids such as methanesulfonic acid, ethanesulfonic acid, and 2-hydroxyethanesulfonic acid can also be used. Among these organic acids, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, 2,5-furandicarboxylic acid, and citric acid are preferred.
[0089] Examples of the base of the pH adjuster used in the polishing composition of this embodiment include alkali metal hydroxides or salts thereof, hydroxides or salts thereof of Group 2 elements, quaternary ammonium hydroxides or salts thereof, ammonia, and amines. Specific examples of alkali metals include potassium and sodium.
[0090] As the pH of the grinding composition increases, the zeta potential of the grinding abrasive surface gradually shifts to a negative value, and the zeta potential of the oxide and the silicon-containing material surface also gradually shifts to a negative value. Therefore, when the pH of the grinding composition is too high (for example, the pH is above 5), the zeta potential of the grinding abrasive surface is likely to become a negative value, and in addition, the zeta potential of the grinding object surface is also likely to be a negative value. Therefore, the electrostatic repulsion between the grinding abrasive and the grinding object (including oxides and silicon-containing materials) becomes larger, so that the grinding speed of the silicon-containing material and the oxide is greatly reduced at the same time, and it is difficult to improve the grinding speed ratio of the oxide relative to the silicon-containing material. Therefore, it becomes unfavorable to use the silicon-containing material as a grinding stop layer when grinding the oxide, and it is also unfavorable to shorten the time spent in the grinding process.
[0091] The pH of the grinding composition of the present embodiment is in the range of 1.5 or more and 4.5 or less. The surface zeta potential of the grinding abrasive in the environment is positive, and there is an electrostatic attraction between the negatively charged grinding object (such as oxide). Therefore, the grinding speed of the oxide can be improved. Furthermore, under acidic conditions, the silica particles as grinding abrasives are not easy to aggregate due to electrostatic repulsion, and the storage stability of the grinding composition can be greatly improved. More specifically, the pH of the grinding composition of the present embodiment is preferably 1.8 or more, more preferably 2 or more, and more preferably 2.5 or more. In addition, the pH of the grinding composition of the present embodiment is preferably 4.2 or less, more preferably 4 or less, and more preferably 3.5 or less.
[0092] In some embodiments, the pH of the polishing composition may be 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, 2.0 or more, 2.1 or more, 2.2 or more, 2.3 or more, 2.4 or more, 2.5 or more, 2.6 or more, or 2.7 or more. In some embodiments, the pH of the polishing composition may be 4.5 or less, 4.4 or less, 4.3 or less, 4.2 or less, 4.1 or less, 4.0 or less, 3.9 or less, 3.8 or less, 3.7 or less, 3.6 or less, or 3.5 or less.
[0093] When the pH of abrasive composition is too high, the grinding rate of oxide is greatly reduced, and oxide is also greatly reduced relative to the grinding rate ratio of silicon-containing material. Therefore, it becomes unfavorable to use silicon-containing material as the grinding stop layer when oxide is ground, and is also unfavorable for the shortening of the time spent in the grinding process. And then, when the pH value of abrasive composition is too high, the storage stability of abrasive composition may also be reduced. On the other hand, when the pH value of abrasive composition is too low, the safety of process can be reduced, and the burden of waste liquid treatment will increase.
[0094] [Dispersion medium]
[0095] The abrasive composition of the present embodiment includes a dispersion medium (also referred to as a "solvent"). The dispersion medium can be used to disperse or dissolve the components in the abrasive composition. In the present embodiment, the abrasive composition may also include water as a dispersion medium. From the viewpoint of suppressing the effects of other components, water containing no impurities as much as possible is preferred. More specifically, it is preferred to remove impurity ions with an ion exchange resin and then remove foreign matter through a filter to obtain pure water or ultrapure water or distilled water.
[0096] [Other ingredients]
[0097] The polishing composition used in the polishing method of the present invention may contain other components such as a chelating agent, an oxidizing agent, a metal anticorrosive agent, a preservative, and a mildew preventive, as required.
[0098] [Polishing method and substrate manufacturing method]
[0099] As described above, the polishing composition of the present invention is particularly suitable for polishing a substrate containing a silicon-containing material and an oxide. Therefore, the present invention provides a polishing method, which uses the polishing composition of the present invention to polish a polishing object containing a silicon-containing material and an oxide. For example, the polishing object may include a substrate formed of a silicon-containing material and an oxide layer formed on the substrate. As a specific example of an oxide, silicon oxide can be cited. As a specific example of a silicon-containing material, a molecular formula Si x Ge 1-x For the silicon-containing material shown, x=0.1 to 1. In addition, the present invention provides a method for manufacturing a substrate, which comprises the step of polishing a substrate comprising a silicon-containing material and a germanium oxide material using the polishing composition of the present invention.
[0100] When grinding a grinding object comprising a silicon-containing material and an oxide, in order to use the silicon-containing material as a grinding stop layer during oxide grinding, the greater the difference between the removal rate of the oxide and the removal rate of the silicon-containing material, the more preferred. That is, the higher the grinding selectivity ratio (grinding rate ratio or removal rate ratio) of the oxide relative to the silicon-containing material, the better. More specifically, when grinding a grinding object comprising a silicon-containing material and an oxide under a specific grinding pressure (e.g., 1.0 psi), the ratio (R1 / R2) of the removal rate R1 of the oxide relative to the removal rate R2 of the silicon-containing material is 10 or more, and the higher the ratio R1 / R2, the more preferred. In some embodiments of the present invention, when the grinding pressure is 1.0 psi, the removal rate of the oxide by the grinding composition is the first removal rate R1, the removal rate of the silicon-containing material by the grinding composition is the second removal rate R2, and the ratio (R1 / R2) of the first removal rate relative to the second removal rate is preferably 10 or more, more preferably 15 or more, further preferably 20 or more, and particularly preferably 30 or more. The upper limit of the ratio (R1 / R2) of the first removal rate to the second removal rate is not particularly limited, and the higher the better. For example, the ratio (R1 / R2) can be set to 200 or less.
[0101] As the grinding device used in the grinding step, a grinding device used in a conventional chemical mechanical grinding process can be used. The grinding device is provided with a carrier for holding the grinding object and a motor capable of changing the rotation speed, and has a grinding plate to which a grinding pad (or grinding cloth) can be attached.
[0102] The polishing pad is not particularly limited, and may be a common nonwoven fabric, a polyurethane resin pad, a porous fluororesin pad, etc. Furthermore, the polishing pad may be grooved as required, so that the polishing composition can be accumulated in the grooves of the polishing pad.
[0103] The parameters of the grinding step are not particularly limited and can be adjusted according to actual needs. For example, the rotation speed of the grinding plate can be set to 10 to 500 rpm, the rotation speed of the carrier can be set to 10 to 500 rpm, the flow rate of the grinding composition can be set to 10 to 500 mL / min, the grinding pressure can be set to 0.1 to 10 psi, and the grinding time can be set to 10 seconds to 30 minutes. The method of supplying the grinding composition to the grinding pad is also not particularly limited, for example, a continuous supply method based on a pump or the like can be adopted.
[0104] After the polishing step is completed, the polished object is cleaned in a stream of water, and water droplets attached to the polished object are shaken off and dried using a spin dryer or the like, thereby obtaining a substrate with a flat surface and no height difference.
[0105] Example
[0106] The present invention is described in detail by the following examples and comparative examples, but the protection scope of the present invention is not limited to the following examples. In addition, in this specification, unless otherwise specified, the operation and the measurement of physical properties are carried out under the conditions of room temperature (20-25°C) / relative humidity 40-50%RH.
[0107] [Preparation of Abrasive Composition]
[0108] According to the composition shown in Table 1 below, abrasive grains, additives and pH adjusters were mixed in a dispersion medium (ultrapure water) (mixing temperature: about 25°C, mixing time: about 10 minutes) to prepare an abrasive composition. The pH of the abrasive composition was confirmed with a pH meter (LAQUA, manufactured by Horiba, Ltd.) (the temperature of the abrasive composition during pH measurement was 25°C). In addition, "-" in Table 1 means that the component was not added. The details of each component in Tables 1 and 2 are as follows.
[0109] [Grinding abrasive and additive molecules]
[0110] Abrasive a: Colloidal silica (primary particle size: 30 nm, secondary particle size: 60 nm, silanol group density on the abrasive surface: 1.5 / nm 2 )
[0111] Abrasive b: Colloidal silica (primary particle size: 35 nm, secondary particle size: 70 nm, silanol group density on the abrasive surface: 4.4 / nm 2 )
[0112] Abrasive c: Colloidal silica (primary particle size: 35 nm, secondary particle size: 70 nm, silanol group density on the abrasive surface: 4.5 / nm 2 )
[0113] Additive A: Glycerol (MW: 92 g / mol)
[0114] Additive B: Polypropylene glycol 400 (MW: 446 g / mol)
[0115] Additive C: Polyglycerin #310 (MW: 314 g / mol)
[0116] Additive D: Polyglycerin #500 (MW: 462 g / mol)
[0117] Additive E: Polyglycerin #750 (MW: 759 g / mol)
[0118] Additive F: Polyglycerin 40 (MW: 2978 g / mol)
[0119] Additive G: Polyglyceryl-4lauryl ether (MW: 482 g / mol)
[0120] Additive H: Polyglyceryl-10lauric acid ester (MW: 940g / mol)
[0121] Additive I: Polyglyceryl-10oleic acid ester (MW: 1022 g / mol)
[0122] HNO3: Nitric acid (concentration: 70%)
[0123] Additive J: Polyglyceryl-4lauric acid ester (MW: 432g / mol)
[0124] Additive K: Polyglyceryl-6lauric acid ester (MW: 548 g / mol)
[0125] Additive L: Polytetrahydrofuran (=polytetramethylene ether glycol; MW: 250 g / mol).
[0126] It should be noted that the additive B is equivalent to R in the above formula (I). 1 H, R 2 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 A compound wherein n is an integer of 2 to 20 and m, p, q and r are all 0. In addition, the above additives C to F correspond to R in the above formula (I). 1 and R 2 are H; n is an integer of 2 to 40; m and p are both 0, q and r are 1. The above-mentioned additive G corresponds to R in the above-mentioned formula (I) 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2is H; n is an integer of 2 to 20; m and p are both 0, and q and r are both 1. The above additives H to K correspond to R in the above formula (I) 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2 is H; n is an integer of 2 to 20; m, q and r are all 1, and p is 0. The above-mentioned additive L corresponds to R in the above-mentioned formula (I) 1 and R 2 The compound wherein all of them are H; n is an integer of 2 to 20; m, p and q are all 0, and r is 2.
[0127] [Measurement of Secondary Particle Size of Polishing Abrasive Grains]
[0128] The average secondary particle size (unit: nm) of the abrasive grains (colloidal silica) was measured as a volume average particle size (volume-based arithmetic mean diameter; Mv) using a dynamic light scattering particle size distribution measuring device (manufactured by Nikkiso Co., Ltd.: UPA-UT151) for the abrasive grain samples. The results of the secondary particle size measurement of the abrasive grains are recorded in Tables 1 and 2.
[0129] [Measurement of surface zeta potential]
[0130] The surface zeta potential of the polishing abrasive grains contained in the polishing composition was measured by a multiple frequency electro-acoustic method using an interfacial potential analyzer (Zeta Probe Analyzer manufactured by Colloidal Dynamics).
[0131] [Measurement of silanol group density on the surface of polishing abrasive grains]
[0132] First, 1.50 g of colloidal silica as a solid component is measured and placed in a 200 mL beaker. After adding about 100 mL of pure water to make a slurry, 30 g of sodium chloride is added to dissolve it. Then, 1 N hydrochloric acid is added to adjust the pH of the slurry to about 3.0 to 3.5, and then pure water is added to make the volume of the slurry 150 mL. The slurry is adjusted to 4.0 with 0.1 N sodium hydroxide at 25 ° C using an automatic titration device (manufactured by Hiranuma Sangyo Co., Ltd., COM-1700), and then the volume V (unit: L) of the 0.1 N sodium hydroxide solution required to increase the pH from 4.0 to 9.0 is measured by pH titration. The silanol group density on the surface of the grinding abrasive can be calculated using the following formula. The measurement results of the silanol group density on the surface of the grinding abrasive are recorded in the grinding abrasive a to grinding abrasive c columns in the detailed contents of each component mentioned above ([grinding abrasive and additive molecules]).
[0133] ρ=(c×V×NA×10 -21 ) / (C×S)
[0134] In the above formula,
[0135] ρ represents the silanol group density on the surface of the abrasive grains (unit: pcs / nm 2 );
[0136] c represents the concentration of the sodium hydroxide solution used in the titration (unit: mol / L);
[0137] V represents the volume of sodium hydroxide solution required to increase the pH from 4.0 to 9.0 (unit: L);
[0138] N A represents Avogadro's constant (unit: per mol);
[0139] C represents the total mass (solid content) of silica (unit: g);
[0140] S represents the BET specific surface area of silica (unit: nm 2 / g).
[0141] [Determination of removal rate]
[0142] The polishing composition obtained above was used to measure the polishing performance of silicon germanium (Si) with a diameter of 300 mm under the following polishing conditions. x Ge 1-x ) (specifically x = 0.75) substrate (manufacturer: Silicon Valley Microelectronic, Inc.; film thickness: )、300mm diameter polysilicon (Poly-Si) substrate (manufacturer: Silicon Valley Microelectronic, Inc.; film thickness: ) and a 300 mm diameter silicon oxide (specifically, silicon oxide derived from tetraethyl orthosilicate (TEOS)) substrate (hereinafter referred to as "TEOS substrate"; manufacturer: Silicon Valley Microelectronic, Inc.; film thickness: The removal rates of the polishing are shown in Tables 1 and 2.
[0143] Polishing device: Single-side CMP polishing device (FREX 300E; manufactured by Ebara Manufacturing Co., Ltd.)
[0144] Polishing pad: Polyurethane pad
[0145] Plate speed: 90rpm
[0146] Carrier speed: 90rpm
[0147] Flow rate of polishing composition: 300 mL / min
[0148] Grinding time: 60 seconds
[0149] Grinding pressure: 1.0 psi (about 6.9 kPa).
[0150] The thickness of the polishing object before and after polishing was measured using a film thickness measurement system (manufactured by KLA-Tencor Corporation; ASET F5x). The removal rate was calculated using the following formula.
[0151] Removal rate = {[thickness before grinding] - [thickness after grinding]} / [processing time]
[0152] In the above formula, the unit of thickness is The unit of treatment time is minutes, and the unit of removal rate is ( / minute). It should be noted that
[0153] [Calculation of removal rate ratio]
[0154] The polishing step is performed at the above polishing pressure (i.e., 1.0 psi), and the removal rate R of the silicon germanium substrate under the polishing pressure is calculated using the above formula. SiGe , removal rate R of polysilicon substrate Si , Removal rate R of silicon oxide substrate TEOS Calculate the removal rate R of the silicon oxide substrate when the polishing pressure is 1.0 psi TEOS Removal rate R relative to silicon germanium substrateSiGe The ratio (R TEOS / R SiGe ), removal rate R of silicon oxide substrate TEOS Relative removal rate R of polysilicon substrate Si The ratio (R TEOS / R Si ). The ratio (R TEOS / R SiGe ) and (R TEOS / R Si ) can be used to indicate the grinding selectivity of oxide to silicon-containing material at a specific grinding pressure (i.e., 1.0 psi). The larger the removal rate ratio, the larger the grinding selectivity of oxide to silicon-containing material. The removal rate ratio (R TEOS / R SiGe ) and (R TEOS / R Si ) are also shown in Table 1 and Table 2.
[0155] In this specification, it should be noted that the removal rate of the oxide by the polishing composition is the first removal rate R1, and the first removal rate R1 corresponds to the removal rate R1 of the silicon oxide substrate in the embodiment. TEOS In addition, the removal rate of the silicon-containing material by the polishing composition is a second removal rate R2, and the second removal rate R2 may correspond to the removal rate R of the silicon germanium substrate. SiGe Or the removal rate R of the polysilicon substrate Si The ratio of the first removal rate to the second removal rate (R1 / R2) may correspond to the ratio of the removal rate of the silicon oxide substrate to the removal rate of the silicon germanium substrate (R TEOS / R SiGe ) or the ratio of the removal rate of the silicon oxide substrate to the removal rate of the polysilicon substrate (R TEOS / R Si ).
[0156] [Table 1]
[0157]
[0158] [Table 2]
[0159]
[0160] Refer to Examples 1 to 8 in Table 1, Examples 11 to 13 in Table 2, and Comparative Example 1 in Table 1. Except that Comparative Example 1 does not use an additive having a structure represented by formula (I), other experimental conditions of Examples 1 to 8, 11 to 13 and Comparative Example 1 are the same or similar. According to the experimental results, the removal rate ratio (R TEOS / R SiGe ) and (RTEOS / R Si ) were 2.3 and 3.6, respectively, that is, they were all less than 10. In contrast, Examples 1 to 8 all used additives having the structure represented by formula (I) (i.e., additives B, C, D, E, F, G, H, and I), and the removal rate ratios (R TEOS / R SiGe ) and (R TEOS / R Si ) are all greater than 10. It can be seen that the polishing composition using the additive having the structure represented by formula (I) can greatly improve the polishing selectivity of TEOS relative to silicon germanium or silicon.
[0161] Refer to Examples 1 to 8 in Table 1, Examples 11 to 13 in Table 2, and Comparative Example 2 in Table 1. Except that the additive used in Comparative Example 2 is not an additive that satisfies all the conditions of the structure shown in Formula (I), the other experimental conditions of Examples 1 to 8, 11 to 13 and Comparative Example 2 are the same or similar. According to the experimental results, the removal rate ratio (R TEOS / R SiGe ) and (R TEOS / R Si ) are 5.9 and 6.2 respectively, that is, both are less than 10. It should be noted that the additive used in the comparative example is glycerol (weight average molecular weight is 92), and the structure of glycerol is similar to the structure shown in formula (I), the difference is that the main chain segment is relatively short, the hydrophilicity of the additive molecule is relatively strong, and the weight average molecular weight is also relatively small. It can be seen that although the structures of the additives used are similar, when the weight average molecular weight of the additive molecule is too small or the hydrophilicity is too strong, the hydrophobic segments of the additive molecule will become too few, which is not enough to effectively improve the grinding selectivity of TEOS relative to silicon germanium or silicon. In addition, compared with the removal rate R of the TEOS substrate in Comparative Example 1 without using an additive, TEOS ( / minute), the removal rate R of the TEOS substrate of Comparative Example 2 is TEOS ( Therefore, it can be seen that the use of additives may also lead to a decrease in the removal rate of oxides.
[0162] Refer to Example 4 and Comparative Example 3 in Table 1. Except that the surface zeta potential of the grinding abrasive b used in Comparative Example 3 is negative (i.e. -132.0 mV), the other experimental conditions of Example 4 and Comparative Example 3 are the same or similar. According to the experimental results, the removal rate ratio (R TEOS / R SiGe ) and (R TEOS / R Si) are 0.7 and 0.6 respectively, that is, they are both much smaller than 10. It should be noted that, in Comparative Example 3, the removal rate of the TEOS substrate is greatly reduced. TEOS ( / min) is less than the removal rate R of the silicon germanium substrate SiGe ( / min) and the removal rate of polysilicon substrate R Si ( / minute).
[0163] Refer to Example 4 and Comparative Example 4 in Table 1. The silanol group density on the surface of the polishing abrasive c used in Comparative Example 4 was 4.5 pcs / nm. 2 In addition, the other experimental conditions of Example 4 and Comparative Example 4 are the same or similar. According to the experimental results, the removal rate ratio (R TEOS / R SiGe ) and (R TEOS / R Si ) are 4.6 and 9.3 respectively, that is, both are less than 10. It can be seen that when using polishing abrasive grains with too high a silanol group density, it is difficult to effectively improve the polishing selectivity of TEOS relative to silicon germanium or silicon. Furthermore, in Example 4 and Comparative Example 4, the removal rate R of the TEOS substrate is TEOS They are / minute and / min. That is, the removal rate R of the TEOS substrate of Comparative Example 4 is TEOS It is only about 1 / 3 of that in Example 4. It can be seen from this that when polishing abrasive grains with too high a silanol group density are used, the removal rate of the TEOS substrate is greatly reduced, thereby increasing the time required for the polishing process.
[0164] Refer to Examples 4, 9, 10 and Comparative Examples 5 and 6 in Table 1. Except that the pH values of Examples 4, 9, 10 and Comparative Examples 5 and 6 are 2.0, 3.0, 4.0, 5.0 and 7.0 respectively, the other experimental conditions of Examples 4, 9, 10 and Comparative Examples 5 and 6 are the same or similar. It should be noted that: all of them use grinding abrasive a, but the surface zeta potential of the grinding abrasives in Comparative Examples 5 and 6 are negative (Comparative Examples 5 and 6 are -87.8 mV and -240.7 mV respectively), and the surface zeta potential of the grinding abrasives in Examples 4, 9 and 1 are positive (Examples 4, 9 and 10 are 36.7 mV, 33.9 mV and 11.8 mV respectively). It can be seen that even if the same grinding abrasive is used, the surface zeta potential of the grinding abrasive is different under different pH conditions. According to the experimental results, the ratio of the removal rate (R TEOS / R SiGe ) and (R TEOS / RSi ) are 0.5 and 0.4 respectively, and the removal rate ratio (R TEOS / R SiGe ) and (R TEOS / R Si ) are 1.0 and 0.9 respectively. That is, in Comparative Examples 5 and 6, the removal rate ratio (R TEOS / R SiGe ) and (R TEOS / R Si ) are far less than 10. Furthermore, in Comparative Examples 5 and 6, the removal rate of the TEOS substrate is greatly reduced, so the removal rate R of the TEOS substrate is TEOS (respectively / minute, / min) are the removal rates R of silicon germanium substrate SiGe (respectively / minute, / min) and the removal rate of polysilicon substrate R Si (respectively / minute, / minute) or less.
[0165] Refer to Examples 1 to 10 in Table 1 and Examples 11 to 13 in Table 2. The polishing compositions used in Examples 1 to 10 respectively contain polishing abrasives (i.e., polishing abrasives a) satisfying a specific range of silanol group density, and additives (i.e., additives B, C, D, E, F, G, H, I, J, K, L) satisfying all the conditions of the structure represented by the above formula (I), and the pH of the polishing composition satisfies the above specific acidic range (i.e., 2.0, 3.0, 4.0). According to the experimental results, the removal rate ratio (R TEOS / R SiGe ) and (R TEOS / R Si ) are all greater than 10. It can be seen that under specific pH conditions, when a polishing composition obtained by combining an additive having a structure represented by formula (I) with specific polishing abrasive grains is used, the polishing selectivity of TEOS relative to silicon germanium or silicon is greatly improved. In addition, compared with the removal rate R of the TEOS substrate of Comparative Example 2, TEOS ( / min) compared with the removal rate R of the TEOS substrate of Examples 1 to 6. TEOS (respectively / minute, / minute, / minute, / minute, / minute, This shows that by adjusting the type and content of additives, the removal rate of oxides can be further increased and the time spent in the polishing process can be shortened.
[0166] In summary, the grinding composition of the present invention comprises grinding abrasive particles that meet specific conditions and additives with specific structures, and under a specific pH environment, the grinding selectivity ratio of oxides relative to silicon-containing materials can be greatly improved. When the grinding composition of the present invention is used to grind a grinding object comprising silicon-containing materials and oxides, the silicon-containing material can be used as a grinding stop layer during oxide grinding. Therefore, the surface flatness of the grinding object can be made good, the complexity of the process can be simplified, and the time and cost of production can be reduced. Furthermore, for the grinding composition of the present invention, the removal rate of oxides can be adjusted by adjusting the type and content of additives. For example, the removal rate of oxides can be further improved, and the time spent in the grinding process can be shortened.
[0167] Furthermore, the polishing composition of the present invention can be used in a chemical mechanical polishing process and is useful for obtaining a substrate having a flat surface, and thus has industrial applicability.
[0168] The present invention is disclosed as above by using several preferred embodiments, but these are not intended to limit the present invention. Those skilled in the art may add any changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention is based on the scope defined by the aforementioned claims.
[0169] This application is based on the foreign language specification submitted in conjunction with the application of Japanese Patent Application No. 2019-209538 filed on November 20, 2019, and the disclosed contents thereof are incorporated herein by reference in their entirety.
Claims
1. A polishing composition, which is composed of polishing abrasive particles, additive molecules, pH adjusters, and dispersion media, or is composed of polishing abrasive particles, additive molecules, pH adjusters, dispersion media, and other ingredients, The grinding abrasive particles are silicon dioxide particles, and the silanol group density on the surface of the silicon dioxide particles is 0 to 3.0 per nm. 2 , The silanol group density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration; The additive molecule has a structure shown in formula (I), In formula (I), R 1 H, C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl, or C2~C 18 Straight chain alkenyl, R 2 For H, n is an integer from 2 to 40, m is 0 or 1, p is 0, q is 1, r is 1, When m is 1, R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl; The content of the additive molecules is 50 ppm by weight or more and 2000 ppm by weight or less relative to the total weight of the polishing composition. The pH adjuster is used to adjust the pH of the polishing composition to a range of 2.1 or more and 3.9 or less; The other ingredients are at least one selected from the group consisting of oxidants, metal corrosion inhibitors, preservatives, and mildew inhibitors. The zeta potential of the polishing abrasive is greater than or equal to +30 mV and less than or equal to +60 mV. The pH of the polishing composition is 2.1 or more and 3.9 or less.
2. The polishing composition according to claim 1, wherein The content of the additive molecules is 50 ppm by weight or more and 1000 ppm by weight or less relative to the total weight of the polishing composition.
3. The polishing composition according to claim 1, wherein The weight average molecular weight of the additive molecule is 100 or more and 600 or less.
4. The polishing composition according to claim 1, wherein In formula (I), R 1 and R 2 All are H; n is an integer from 2 to 40; And m and p are both 0, q and r are both 1.
5. The polishing composition according to claim 1, wherein In formula (I), R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2 is H; n is an integer from 2 to 20; And m and p are both 0, q and r are both 1.
6. The polishing composition according to claim 1, wherein In formula (I), R 1 C1~C 18 Straight chain alkyl, C3~C 18 Branched alkyl or C2~C 18 Straight chain alkenyl, R 2 is H; n is an integer from 2 to 20; And m, q and r are all 1, and p is 0.
7. The abrasive composition according to claim 1, wherein The content of the abrasive grains is 0.1 to 10 wt % relative to the total weight of the abrasive composition.
8. A polishing method comprising the step of polishing an object to be polished using the polishing composition according to any one of claims 1 to 7, wherein the material of the object to be polished comprises an oxide and a silicon-containing material, wherein the silicon-containing material is Si x Ge 1-x Indicates, and x=0.1~1.
9. The grinding method according to claim 8, wherein: When the polishing pressure is 1.0 psi, the removal rate of the oxide by the polishing composition is a first removal rate R1, the removal rate of the silicon-containing material by the polishing composition is a second removal rate R2, and the ratio R1 / R2 of the first removal rate to the second removal rate is greater than 10.
10. A method for manufacturing a substrate, comprising: The process of preparing a substrate, wherein the surface of the substrate comprises an oxide and a silicon-containing material, wherein the silicon-containing material is Si x Ge 1-x Indicates, and x = 0.1 ~ 1; A step of polishing the substrate using the polishing composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Device for automatically wrapping metal leaf with coated fabric
CN201311842Y
Image quality inspection system and display control method
JP2019209538A
Polishing solution and polishing method
WO2019030865A1
Slurry and polishing method
WO2019044978A1